Gender Aspects of Managerial Communication - Pauknerová (Array, 2007)
Quantity and quality of communication in managerial work depend on personality traits, interpersonal and management skills as well as leadership styles of managers. Many researchers also suppose that gender plays a significant role in this respect. The aim of this research was to analyze differences among men and women in managerial positions. Psychological testing and observation of managers’ performance in experimental situations modeling managerial decision making and acting were used as methods. Gender differences in personality traits, interpersonal and management skills were identified based on data collected from a sample of male and female managers from the financial sector. Two studies were done to analyze differences among men and women. The first one suggests that male and female managers differ in some personality traits. The second one suggests that there are no significant differences between men and women in managerial behavior and leadership skills.